IV thrombolysis and renal function - Gensicke, Henrik; Zinkstok, Sanne M.; Roos, Yvo B.; Seiffge, David; Ringleb, Peter A.; Artto, Ville; Putaala, Jukka; Haapaniemi, Elena; Leys, Didier; Bordet, Régis; Michel, Patrik; Odier, Céline; et al. (Neurology, 2013)
Objective: To investigate the association of renal impairment on functional outcome and complications in stroke patients treated with IV thrombolysis (IVT). - Methods: In this observational study, we compared the estimated glomerular filtration rate (GFR) with poor 3-month outcome (modified Rankin Scale scores 3-6), death, and symptomatic intracranial hemorrhage (sICH) based on the criteria of the European Cooperative Acute Stroke Study II trial. Unadjusted and adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Patients without IVT treatment served as a comparison group. - Results: Among 4,780 IVT-treated patients, 1,217 (25.5%) had a low GFR (<60 mL/min/1.73 m2). A GFR decrease by 10 mL/min/1.73 m2 increased the risk of poor outcome (OR [95% CI]): (ORunadjusted 1.20 [1.17-1.24]; ORadjusted 1.05 [1.01-1.09]), death (ORunadjusted 1.33 [1.28-1.38]; ORadjusted 1.18 [1.11-1.249]), and sICH (ORunadjusted 1.15 [1.01-1.22]; ORadjusted 1.11 [1.04-1.20]). Low GFR was independently associated with poor 3-month outcome (ORadjusted 1.32 [1.10-1.58]), death (ORadjusted 1.73 [1.39-2.14]), and sICH (ORadjusted 1.64 [1.21-2.23]) compared with normal GFR (60-120 mL/min/1.73 m2). Low GFR (ORadjusted 1.64 [1.21-2.23]) and stroke severity (ORadjusted 1.05 [1.03-1.07]) independently determined sICH. Compared with patients who did not receive IVT, treatment with IVT in patients with low GFR was associated with poor outcome (ORadjusted 1.79 [1.41-2.25]), and with favorable outcome in those with normal GFR (ORadjusted 0.77 [0.63-0.94]). - Conclusion: Renal function significantly modified outcome and complication rates in IVT-treated stroke patients. Lower GFR might be a better risk indicator for sICH than age. A decrease of GFR by 10 mL/min/1.73 m2 seems to have a similar impact on the risk of death or sICH as a 1-point-higher NIH Stroke Scale score measuring stroke severity.
Gesehen am 04.02.2020